Rancang Bangun Miniatur Pembangkit Listrik Tenaga Mikrohidro Dibengkel Teknik Listrik Universitas Batanghari Jambi - Ottentri Ottentri; Hendi Matalata (Journal of Electrical Power Control and Automation (JEPCA), 2019)
The need for electrical energy is a necessity that can not be ditawar–tawar anymore for a life worthy of every person in this day. Generally, remote rural areas located in mountainous areas have a large potential of water energy, so that the hydroelectric power plant is one of the energy sources that can be developed. Jambi is an area covered with Batanghari River flows. This research aims to know how the work process of Microhydro power plant.  Components of the essential components of miniature microhydro power plants are reservoirs, rapid pipes, turbines, generators where these components are not loose bias, interrelated to one another. Round of Tubin obtained from the experiment is 400 rpm with water discharge 0.0016 m3/s. The maximum voltage generated by the generator is 18 volts. Voltage generated from the generator to charging the Batrai used inverter of 13.1 volts. The load will remain on even though the main energy source is the generator stop in the same, because the energy of the second is Batrai.